The effect of philosophical dualism in the problem of animal ethics - Henríquez R., Alfonso (Acta Bioethica, 2014)
In the moral field, there is a separation between animals and human beings, express philosophically in the idea of ontological dualism. One of the consequences of this view is the justification made in bioethics for the experimentation with living animals. Nevertheless, such separation has no relation with the place human beings hold within the living order, which opens a space for the reconsideration of the moral statute of animals.